Photocycle Dynamics of the Archaerhodopsin 3 Based Fluorescent Voltage Sensor QuasAr1 - Penzkofer, Alfons (Int J Mol Sci, 2019)
The retinal photocycle dynamics of the fluorescent voltage sensor QuasAr1 (Archaerhodopsin 3 P60S-T80S-D95H-D106H-F161V mutant from Halorubrum sodomense) in pH 8 Tris buffer was studied. The samples were photoexcited to the first absorption band of the protonated retinal Schiff base (PRSB) Ret_580 (absorption maximum at λ(max) ≈ 580 nm), and the retinal Schiff base photoisomerization and protonation state changes were followed by absorption spectra recordings during light exposure and after light exposure. Ret_580 turned out to be composed of two protonated retinal Schiff base isomers, namely Ret_580(I) and Ret_580(II). Photoexcitation of Ret_580(I) resulted in barrier-involved isomerization to Ret_540 (quantum yield ≈ 0.056) and subsequent retinal proton release leading to Ret_410 deprotonated retinal Schiff base (RSB). In the dark, Ret_410 partially recovered to Ret_580(I) and partially stabilized to irreversible Ret_400 due to apoprotein restructuring (Ret_410 lifetime ≈ 2 h). Photoexcitation of Ret_580(II) resulted in barrier-involved isomerization to Ret_640 (quantum yield ≈ 0.00135) and subsequent deprotonation to Ret_370 (RSB). In the dark, Ret_370 partially recovered to Ret_580(II) and partially stabilized to irreversible Ret_350 due to apoprotein restructuring (Ret_370 lifetime ≈ 10 h). Photocycle schemes and reaction coordinate diagrams for Ret_580(I) and Ret_580(II) were developed and photocyle parameters were determined.